ANALISIS KUALITAS PELAYANAN DI MASA PANDEMI COVID-19 (STUDI KASUS PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BUKITTINGGI) - Eka Putra; Roni Ekha Putera (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2022)
This study is a research with a qualitative approach that describes how to improve compliance with public service standards by looking at the service quality of the Population and Civil Registration Service in improving services during the Covid-19 Pandemic in Bukittinggi City. Based on the results of the analysis, the quality of this service does not appear by itself, there is the involvement of the community and the Population and Civil Registry Office of the City of Bukittinggi in this matter. There are 5 indications in the quality of this service, namely in tangible terms the Population and Civil Registry Office of Bukittinggi City in providing physical services to the community, in addition to providing technical guidance to employees is also physical evidence that is very helpful in supporting the services of the Population and Civil Registry Office of Bukittinggi City to the public. Bukittinggi community.In terms of reliability, the Population and Civil Registry Office of the City of Bukittinggi to the people of Bukittinggi has been reliable in providing services, this can be seen from the satisfaction felt by the people of Bukittinggi towards the services of the Department of Population and Civil Registration of the City of Bukittinggi to the people of Bukittinggi, in terms of responsiveness of the Department of Population and Civil Registry. The city of Bukittinggi serves well and is responsive in responding to all community problems so as to create comfort in the use of services.